Human Nature and Conduct: An Introduction to Social Psychology - Dewey, John 1859-1952 (New York Prometheus, 2002)
Influential work by the great educator/philosopher maintains that the key to social psychology lies in an understanding of the many varieties of habit; individual mental activity is guided by subordinate factors of impulse and intelligence. His investigation focuses on three main areas of conduct: habit, impulse, and intelligence, with each factor receiving an incisive treatment.
Keywords: 20th Century (1901-2000); Philosophy; Psychology; USA